Inferior plant competitor allocates more biomass to belowground as a result of greater competition for resources in heterogeneous habitats - Zhou, Jian; Ma, Ziwen; Jia, Yuehui; Liu, Jie; Yang, Yuping; Li, Wei; Cui, Lijuan (Frontiers in Plant Science, 2023)
Nutrient heterogeneity in soil widely exists in nature and can have significant impacts on plant growth, biomass allocation, and competitive interactions. However, limited research has been done to investigate the interspecific competitive intensity between two clonal species in a heterogeneous habitat. Therefore, this greenhouse experiment was conducted with two clonal species, Phragmites australis and Scirpus planiculumis, exposed to heterogeneous and homogeneous patches of soil nutrients at five different planting ratios (0:4, 1:3, 2:2, 3:1 and 4:0), to assess the effects of both soil heterogeneity and interspecific competition on plant growth. It was found that soil nutrient heterogeneity significantly enhanced P. australis' interspecific competitive capacity and biomass by promoting a 20% increase in belowground allocation.Interestingly, the planting ratio did not affect the magnitude of this net outcome. In contrast, the superior competitor S. planiculumis did not exhibit significant change of growth indicators to the heterogeneous soil patches. These findings imply that the uncertainties associated with human-induced redistribution of plant species may lead to a shift in dominance from other species to those like P. australis, which have strong nutrient foraging abilities in response to heterogeneity in emergent wetland plant communities.